Study of the effect of sawteeth on fast ions and neutron emission in MAST using a neutron camera. (29th March 2018) - Cecconello, M; Sperduti, A
Abstract: The effect of the sawtooth instability on the confinement of fast ions on MAST, and the impact it has on the neutron emission, has been studied in detail using the TRANSP/NUBEAM codes coupled to a full orbit following code. The sawtooth models in TRANSP/NUBEAM indicate that, on MAST, passing and trapped fast ions are redistributed in approximately equal number and on a level that is consistent with the observations. It has not been possible to discriminate between the different sawtooth models since their predictions are all compatible with the neutron camera observations. Full orbit calculations of the fast ion motion have been used to estimate the characteristic time scales and energy thresholds that according to theoretical predictions govern the fast ions redistribution: no energy threshold for the redistribution for either passing and trapped fast ions was found. The characteristic times have, however, frequencies that are comparable with the frequencies of a m  = 1, n  = 1 perturbation and its harmonics with toroidal mode numbers n = 2, …, 4, suggesting that on spherical tokamaks, in addition to the classical sawtooth-induced transport mechanisms of fast ions by attachment to the evolving perturbation and the associated E  × B drift, a resonance mechanism between the m  = 1 perturbation and the fast ions orbits might be at play.